Mercury behaviour in the water column of an impacted coastal lagoon: Ria de Aveiro (Portugal) as a case study - Ramalhosa, Elsa (2011)
As mercury presents high toxicity and is of great concern when dealing with protection of human health, mercury pollution related issues are the main subject of this work. At first, two general themes are discussed, namely: I) Mercury: highlights of physicochemical and biogeochemical properties of interest and of the main natural and anthropogenic metal sources; and II) Biogeochemical cycling of mercury in the water column of natural waters. Secondly, a case study performed in Ria de Aveiro (Portugal) during the last 10 years will be presented, focusing on water column processes. Ria de Aveiro is a coastal lagoon, located along the Atlantic Ocean on the north-western coast of Portugal, which was subjected to a discharge of an effluent rich in mercury from a chlor-alkali industry, during more than five decades. In the last seventeen years, the industry changed its technology and the discharge of anthropogenic mercury diminished considerably. However, the dissolved total and reactive mercury concentrations, as well as the total mercury contents determined in the suspended particulate matter, obtained in a particular area of Ria de Aveiro, namely Largo do Laranjo, during the years of 1997 to 2000, are still high in comparison to other locals located world wide. In Largo do Laranjo water column, mercury does not show a conservative behavior, due to the inexistence of a linear relationship between the dissolved total mercury concentrations and salinity. Owing to this, mercury behavior is variable and seems to result from a mixture of different phenomena. One of the most important factors that affect the dissolved mercury behavior is the dissolved organic matter, as a significant correlation is found between both parameters (r=0.788). The mercury partition evaluation performed in Largo do Laranjo water column shows that in both tide conditions, the dissolved and particulate fractions are important for mercury transport and distribution in Largo do Laranjo. However, mercury is more closely associated with the particulate phase (58 to 77%) than with the dissolved fraction. Moreover, this case study also allows verifying that Largo do Laranjo still is a mercury source to the rest of Ria de Aveiro, as the estimated annual mean quantities of mercury that are transported in the dissolved and particulate fractions from the end of Largo do Laranjo, namely Cais do Chegado, to seaward are of 38 and 60 kg, respectively.